Laser-Assisted Facial Contouring Using a Thermally Confined 1444-nm Nd-YAG Laser: A New Paradigm for Facial Sculpting and Rejuvenation - Holcomb, J. David; Turk, Jon; Baek, Sung-Jong; Rousso, Daniel E (Facial Plastic Surgery, 2011)
The micropulsed 1444-nm neodymium-doped lipolysis laser exhibits favorable characteristics for novel application in facial contouring. The study described herein is the first clinical report of laser-assisted facial contouring (LAFC). We retrospectively reviewed records of 478 LAFC patients (mean age 52) who underwent contouring of 1278 individual mid- and lower facial treatment sites over 18 months. Along with clinical assessment, study parameters evaluated among “original” and “modified” (where protocol updates included deep dermal soft tissue coagulation as an optional step) protocol groups included laser power, pulse energy, and total energy delivery as well as lipoaspirate volume at each treatment site. Mean power and pulse energy were similar (within 5%) and total energy use was greater (70% higher for mid- and lower face) in the original protocol group. Lipoaspirate volume was similar for both groups for the midface (within 10%) but elevated in the modified protocol group for the lower face (40% higher). Treatment complications were observed in 47 of 363 treatment sites (13%) in the original and in 12 of 915 treatment sites (1%) in the modified protocol group with the majority (63%) of the complications comprising over- versus undercorrections of desired tissue contour. Clinical efficacy varied with improvements of mid- and/or lower facial contour ranging from marginal to subtle to very apparent. LAFC as detailed herein is a novel treatment modality that enables selective soft tissue removal for greater precision in three-dimensional contouring of the face. Protocol modifications based on laboratory and observed tissue photothermodynamics have improved LAFC safety.
Keywords: Laser lipolysis; facial contouring; midface; jawline; melolabial fold; jowl; three-dimensional